2018
DOI: 10.3926/jotse.312
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on blended learning through the on-line platform, LabLessons, for Chemistry

Abstract: The effectiveness of blended learning was evaluated through the integration of an online chemistry platform, LabLessons. Two modules, Titration and Formation of Hydrogen, were designed by college mentors alongside classroom chemistry teachers to engage and allow high school students to better comprehend these scientific topics.  The pre-lab modules introduced the students to experiments they were expected to perform in class the following day. The modules consisted of an introduction as well as either a visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…2,12,13 These challenges have led many to investigate the possibility of supplementing or replacing traditional laboratories with virtual laboratories. 7,8,11,14,15 Compared to traditional laboratories, computer simulations are more shareable and repeatable since they do not require costly physical materials. Simulations are often used as prelabs because the experiment can be practiced without the hazards of actual chemicals.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,12,13 These challenges have led many to investigate the possibility of supplementing or replacing traditional laboratories with virtual laboratories. 7,8,11,14,15 Compared to traditional laboratories, computer simulations are more shareable and repeatable since they do not require costly physical materials. Simulations are often used as prelabs because the experiment can be practiced without the hazards of actual chemicals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6,10 Previous empirical studies at a high school level have shown that virtual prelabs can improve the understanding and visualization of various chemistry concepts, and better prepare students to conduct physical laboratories more efficiently. 14,15 Gryczka et al 14 and Jihad et al 15 developed an online platform of original, simulated prelabs known as LabLessons, which was integrated into a high school chemistry laboratory course. Here, we aim to further the research of Gryczka et al 14 and Jihad et al 15 with the introduction of two additional modules (Supporting Information Table S1).…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations